Expanded screening for Fabry disease in patients with chronic kidney disease not on dialysis: a multicenter Italian experience - Yuri Battaglia; Federica Baciga; Meilad Shakkour; Savio Russo; Giulia Carnicella; Michela Erlati; Gemma Sartori; Giulia Tronconi; Renzo Mignani; Federico Pieruzzi; Paolo Colomba; Laura Scichilone; et al. (Renal Failure)
Fabry disease (FD) is a progressive, multisystemic X-linked disorder caused by mutations in the GLA gene, often leading to renal failure. Although several screening programs have been conducted, the prevalence of FD in patients with chronic kidney patients who are not dependent on dialysis (NDD-CKD) is likely underestimated due to restrictive inclusion criteria and methodological shortcomings. This study aims to assess the prevalence of FD in NDD-CKD patients using an expanded screening approach. Ongoing outpatients attending Italian nephrology clinics were screened by assay of plasma α-galactosidase A (α-Gal A) activity. Genetic testing was also performed in all females and males with low α-Gal A activity. Inclusion criteria were: (1) females ≥18 years old; (2) males aged between 18 and 70 years; (3) NDD-CKD stages 1–5. Patients with histological diagnosis of glomerulonephritis or diagnosis of autosomal dominant polycystic kidney disease (ADPKD) were excluded. Demographic data and laboratory results were also collected. Among 385 NDD-CKD outpatients, 173 underwent screening. One patient with three family members carrying a novel mutation (c.320 A > G, p.Q107R); one patient with three family members carrying a silent mutation (c.48 T > G, p.L16L) and two patients with a missense mutation (c.376A > G, p.S126G), were identified. Overall, the prevalence of FD was 2.3%, increasing to 5.4% (10 in 183) with family screening. FD may be more common than previously believed, particularly within NDD-CKD populations. FD screening should be expanded to include NDD-CKD patients with known causes of CKD, such as hypertension and diabetes mellitus, and genetic testing should be routinely used for female patients.